How do social and spousal support influence postpartum depression? - SAVE, DİLŞAD (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: Postpartum psychiatric morbidity is one of the most frequent complications of birth, cause of suicides and maternal death. We aimed to determine the prevalence of postpartum depression (PPD) among mothers who gave birth in the last 6 months and also assess the risk factors, particularly poor social and spousal support. Patients and Methods: This is a cross-sectional study. We included 303 mothers who gave birth in the last 6 months attending three family health centers in a district of Istanbul. Stratified sampling method was used. Edinburgh Postpartum Depression Scale, Postpartum Support Scale, The Scale of Perceived Spousal Support Among Women in Early Postpartum Period were administered. Univariate and multivariate statistical analyses were used. Results: Postpartum depression prevalence was 9.9% among the participants. According to multivariate statistical analysis; while a higher income (OR : 0.99) and a higher spousal support score (OR: 0.95) were found as protective factors, actively working (OR :8.63), unplanned pregnancy (OR: 3.21), having a first child compared to having two children (OR: 11.20), having low birth weight infant (OR: 8.33) and unmet social support (OR: 1.02) were risk factors for PPD (p<0.05). Conclusion: Considering the results of this study, increasing family income, social and spousal support, prevention of unplanned pregnancies using effective family planning methods and improving the life prosperity of the women are essential to the decrease of PPD prevalence.
Keywords: Postpartum; Depression; Social support; Spousal support; RISK-FACTORS; PREVALENCE; WOMEN; DISORDERS; MOTHERS